2004
DOI: 10.1111/j.1752-1688.2004.tb01009.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTIVENESS OF POLYACRYLAMIDE (PAM) IN IMPROVING RUNOFF WATER QUALITY FROM CONSTRUCTION SITES1

Abstract: Erosion from construction sites significantly affects water quality in receiving streams. A rainfall simulator was used to evaluate the effectiveness of different methods for controlling erosion from construction sites. Erosion control methods investigated included dry and liquid applications of polyacrylamide (PAM), hydroseed, and straw mulch. Fertilizer was also applied to each plot to examine the effectiveness of the methods in reducing nutrient losses in runoff. Runoff samples were analyzed for total suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 10 publications
(13 reference statements)
1
27
0
Order By: Relevance
“…At 0.75 to 10.5 kg ha -1 (0.67 to 9.4 lb ac -1 ), PAM did not significantly reduce runoff turbidity or sediment loss (Hayes et al 2005). Soupir et al (2004) found that PAM in aqueous form at 1.68 to 6.73 kg ha -1 (1.5 to 6.0 lb ac -1 ) did not significantly reduce TSS compared to a bare control.…”
mentioning
confidence: 86%
“…At 0.75 to 10.5 kg ha -1 (0.67 to 9.4 lb ac -1 ), PAM did not significantly reduce runoff turbidity or sediment loss (Hayes et al 2005). Soupir et al (2004) found that PAM in aqueous form at 1.68 to 6.73 kg ha -1 (1.5 to 6.0 lb ac -1 ) did not significantly reduce TSS compared to a bare control.…”
mentioning
confidence: 86%
“…Toward this, to achieve optimal health, safety, and sustainability in watershed resources, the determination of optimum level, type, and environmentally friendly soil amendments is fundamentally important (Sadeghi et al, 2015). Temporary groundcovers such as straw, compost, hydromulch, or rolled erosion control products have proven effective for controlling erosion on slopes (Benik et al, 2003;Soupir et al, 2004;McLaughlin and Brown, 2006). Considering the increasing amount of organic agricultural and urban wastes, there is an urgent need for a sustainable strategy that allows the management and reduction of these kinds of residues.…”
Section: Introductionmentioning
confidence: 99%
“…Her results parallel others in the literature including those of Roa-Espinosa et al (1999) that optimal overall effectiveness is obtained by combining PAM with a mulch or hydroseeding mix. Another aspect of the study by Soupir et al (2004) worth noting is the difficulty that can occur if the PAM application solution is too concentrated, resulting in restriction of infiltration, thereby generating more runoff and preventing maximum erosion control efficacy or stand establishment. This result is in line with the finding of Lentz (2003) and indicates that for best results, especially in hydroseeding a careful control of PAM concentration is important, as well as provision of enough total solution volume to assure some penetration of the PAM into the surface few millimeters of soil.…”
Section: Pam For Construction Sites and Other Disturbed Landsmentioning
confidence: 99%
“…Flanagan et al (2002a,b) reported good successes applying PAM for erosion control on steep slopes. Soupir et al (2004) investigated a number of PAM-and mulch-based treatments for erosion control on construction sites in Virginia. Her results parallel others in the literature including those of Roa-Espinosa et al (1999) that optimal overall effectiveness is obtained by combining PAM with a mulch or hydroseeding mix.…”
Section: Pam For Construction Sites and Other Disturbed Landsmentioning
confidence: 99%